Adverse events following immunization (AEFIs) in health workers who receive COVID-19 vaccination at Academic Hospital Universitas Gadjah Mada, Yogyakarta - Lestari, Ade Febrina; Sitaresmi, Mei Neni; Haspitaningrum, Anjarsari; Rachmasari, Kusuma Ayu; Wulandari, Ratih; Sari, Shinta Kusumalarna; Ridhayani, Firda (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2023)
COVID-19 is a new viral infection that has become a global pandemic, resulting in extremely high mortality and morbidity rates worldwide, including in Indonesia. Vaccination is one of the strategies for preventing COVID-19 infection promoted by the World Health Organization (WHO) to reduce COVID-19 morbidity and mortality. The Indonesian government supports the implementation of vaccination and conducts mass vaccination as a strategy to overcome the pandemic in Indonesia. The high immunization coverage resulted in increased use of vaccines, and events following immunization (AEFI) also increased. Reports on follow-up AEFI are needed as government policy references and information for the public. This study aims to describe the following events after the COVID-19 vaccine immunization and the incidence of the infection post vaccination. The study design was a cross-sectional study using primary and secondary data. The data were analyzed descriptively and statistically using Chi Square method by identifying association between demographic data and AEFI incidence. A total 131 respondents were included. Most respondents experienced AEFI after giving the first (77.1%) or second (71.9%) vaccine with the Sinovac vaccine. However, all reported mild AEFI. Most reported AEFIs were pain (48.8% and 49.6%), hungry (37.4% and 10.0%), and drowsiness (32.1% and 23.7%) after the first and the second vaccine. In conclusion, the prevalence of AEFI in the first and the second dose of inactivated COVID-19 vaccine is higher than that reported in the clinical trial study although the all AEFIs are considered as mild.